2015
DOI: 10.2166/wp.2015.026
|View full text |Cite
|
Sign up to set email alerts
|

Understanding social acceptability of arsenic-safe technologies in rural Bangladesh: a user-oriented analysis

Abstract: Contamination of shallow tube well drinking water by naturally occurring arsenic is a severe societal and human health challenge in Bangladesh. Multiple technological interventions seeking to ameliorate the problem face hurdles in securing social acceptance, i.e. the willingness of users to receive and use a technology. While most papers focus on expert understanding of social acceptability, this paper analyzes how users themselves understand the factors shaping the social acceptability of safe drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…These technological innovations fall into two categories: first, filter and treatment technologies designed to remove arsenic from contaminated shallow tube well water, such as household and community-level filter systems and, second, alternative safe water options that do not require treatment of arsenic-contaminated water. These include piped water supplies, deep tube wells, improved dug wells, designated safe shallow hand pump tube wells, and rain water harvesting (Hoque et al, 2004;Ahmad et al, 2006;Inauen et al, 2013;Kundu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These technological innovations fall into two categories: first, filter and treatment technologies designed to remove arsenic from contaminated shallow tube well water, such as household and community-level filter systems and, second, alternative safe water options that do not require treatment of arsenic-contaminated water. These include piped water supplies, deep tube wells, improved dug wells, designated safe shallow hand pump tube wells, and rain water harvesting (Hoque et al, 2004;Ahmad et al, 2006;Inauen et al, 2013;Kundu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Confronted with the arsenic crisis, policy actors were evolving a clear preference for community level, non-filter technologies, instead of household filters, in the same period of time as the Sono filter was being developed and deployed. For instance, the deep tube well-a close alternative to shallow hand pump tube well -is now dominant in arsenic mitigation in Bangladesh (Ravenscroft et al, 2014; see also Kundu et al, 2016a). As the analysis has shown, a variety of factors, including lack of support from policy actors and absence of a market, and the need to change existing user practices, hindered successful Sono filter niche formation.…”
Section: Discussionmentioning
confidence: 99%
“…A policy maker from DPHE (25 July, 2013) stated that "regardless of what people expect and prefer, implementing agencies deploy the technologies they want or are suggested by donors, as most projects are donor-funded. Basically, projects enforce users to use a particular technology without keeping in mind what users want" (see also Kundu et al, 2016a). Similarly, three focus group sessions revealed that users urgently needed an arsenic mitigation technology and MSUK provided them with the Sono filter without offering any alternatives.…”
Section: Shaping and Convergence Of Expectationsmentioning
confidence: 99%
See 2 more Smart Citations